Caffeine supplementation affects the immunometabolic response to concurrent training - Rossi, Fabricio Eduardo [UNESP]; Goncalves Panissa, Valeria Leme; Monteiro, Paula Aulves [UNESP]; Gerosa-Neto, Jose [UNESP]; Caperuto, Erico Chagas; Cholewa, Jason Michael; Zagatto, Alessandro Moura [UNESP]; Lira, Fabio Santos [UNESP] (Korean Soc Exercise Rehabilitation, 2017)
The aim of the present study was to investigate the effects of caffeine (CAF) and carbohydrate (CHO) intake on strength performance and its metabolic and inflammatory responses during concurrent training. Seven active males ingested a double-placebo (P), CAF (capsule 5 mg/kg) or CHO (20% maltodextrin solution) supplementation before strength exercise. Participants performed three randomized sessions of 5,000-m high-intensity intermittent aerobic exercise at maximal intensity followed by strength exercise, performing after the P, CHO, and CAF intake. The blood samples were collected before (pre) and immediately after concurrent strength exercise (post). We found a similar number of repetitions and total volume in all supplementation groups. There was a main effect of time on glucose, lactate, and interleukin (IL)-6 (P<0.05). When compared the changes between groups (postvalues minus prevalues), there was lower glucose in CAF group when compared to CHO group (CAF=5.0 +/- 10.4 vs. CHO=27.8 +/- 20 vs. P=15.1 +/- 14, P=0.031) and higher IL-6 levels (CAF=11.9 +/- 9.2 vs. CHO=-2.4 +/- 1.7 vs. P=4.3 +/- 11.7, P=0.017). There was significant interaction for glucose and lactate (P<0.001). In conclusion, CAF and CHO intake did not improve strength performance during concurrent strength training in active males. However, CAF affected immunometabolic responses.
Keywords: Metabolism; Inflammation; Performance; Caffeine